(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
Teaching and learning a foreign language becoming vitally important, since knowing the language is knowing people. With this reason, many scholars and researchers are trying to investigate some similarities and differences between languages. The purpose of this article is to study litotes in both English and Uzbek languages. Litotes is a linguistic device that involves the use of negation to express an idea in a double negative or understatement. This study aims to analyze the use of litotes in English and Uzbek languages from linguapragmatic and linguological perspectives. Moreover, this article analyzes the use of litotes in both languages, examining its functions and subtypes. The findings suggest that while there are similarities between the two languages, there are also significant differences in how litotes is used and perceived. In order to reveal unities and diversities, some methods such as observation and comparison are utilized. Linguistically, the study found that litotes operates differently in each language. In English, litotes often involves the use of double negatives to express an affirmation, while in Uzbek, however, litotes often involves understatement without double negatives. Some example given in this article is taken from literature, prose and poetry to identify it.